Johann Sebastian Bach in seinen Büchern: Gedankengänge durch die Bibliothek des Leipziger Thomaskantors - Marquard, Reiner (Kamprad, 2023)
A study of the religious and theological works in Johann Sebastian Bach's library and their influence on his life, faith, and work